The effects of intergenerational epigenetics of traumatic stress on a sexual defeat rat model - Ngala, Elvis Mbiydzenyuy (Stellenbosch : Stellenbosch University, 2025)
Ngala, E. M. 2025. The Effects of Intergenerational Epigenetics of Traumatic Stress on a Sexual Defeat Rat Model. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0afae107-97c9-4386-b004-33d5656c8922